Sorption des nitrates sur billes de gel de chitosan : Application au traitement des eaux souterraines - Jaâfari, Karim (Université Chouaib Doukkali, Faculté des Sciences, El Jadida, 2001)
Nitrate, contained in surface or ground freswater, can be removed by sorption on protonated cross-linked chitosan gel beads. The sorption capcity, which depends on pH, is large enough to meet the standard of drinkable water. The isothermal equilibrium curves are straight lines, which implies that the removal is independent of the initial concentration. The main reactive process, which probably depends in the secondary ammonium groups, involves all the bead volume and not only is surface. If required, the sorption capacity is easily recovered by increasing pH at 12. The main competitor is fluoride but, even in its presence, the sorption capacity of nitrate remains significant. The sorption kinetics, which can be represented by a mass transfer equation, is not limited by pore or by film diffusion.
Keywords: Chimie; Energétique; Génie des procédés; Nitrate; Sorption; Bille de gel; Chitosan; Eau souterraine